Characterizing spatial tuning functions of neurons in the auditory cortex of young and aged monkeys: a new perspective on old data - Engle, James; Recanzone, Gregg H. (Frontiers in Aging Neuroscience, 2013)
Age-related hearing deficits are a leading cause of disability among the aged. While some forms of hearing deficits are peripheral in origin, others are centrally mediated. One such deficit is the ability to localize sounds, a critical component for segregating different acoustic objects and events, which is dependent on the auditory cortex. Recent evidence indicates that in aged animals the normal sharpening of spatial tuning between neurons in primary auditory cortex to the caudal lateral field does not occur as it does in younger animals. As a decrease in inhibition with aging is common in the ascending auditory system, it is possible that this lack of spatial tuning sharpening is due to a decrease in inhibition at different periods within the response. It is also possible that spatial tuning was decreased as a consequence of reduced inhibition at non-best locations. In this report we found that aged animals did have greater activity throughout the response period, but primarily during the onset of the response. This was most prominent at non-best directions, consistent with the hypothesis that inhibition is a primary mechanism to sharpen spatial tuning curves. We also noted that in aged animals the latency of the response was much shorter than in younger animals, consistent with a decrease in pre-onset inhibition. These results can be interpreted in the context of a failure of the timing and efficiency of feed-forward thalamo-cortical and cortico-cortical circuits in aged animals. Such a mechanism, if generalized across cortical areas, could play a major role in age-related cognitive decline.